Penguatan Karakter Disiplin Siswa melalui Latihan Pranayama - Rudiarta, I Wayan; Pramana, Ida Bagus Kade Yoga (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2025)
This paper aims to publish the results of pranayama training for students in Pasraman Widya Ganesa which has implications for the character of student discipline. Student discipline is indeed an essential thing that attracts attention today. This is a result of the many cases of disciplinary violations by students. Pasraman as a non-formal Hindu educational institution should be present to help strengthen the character of discipline in students. This Pranayama training activity is carried out through several steps until the results are obtained, namely planning activities that are realized in the meeting, then location surveys and application for activity permits, then the implementation of pranayama training which emphasizes four types of pranayama, namely Anuloma Viloma, Bhastrika, Kapalabhati, and Bhramari. After the training, the last step is the evaluation of the training activities. The result of this pranayama training is the strengthening of the disciplined character that already exists in students. The character of discipline is further strengthened after the students are trained to better know themselves in the pranayama practice. Students try to strengthen discipline because of the influence from within, not because there are external factors. Pranayama practice that is carried out regularly and directed trains students to concentrate more, be patient, and undergo the learning process with consistency. During the training, the students are accustomed to arriving on time, following directions seriously, and carrying out each stage of the exercise responsibly, which gradually forms a more disciplined pattern of behavior.